Burr knots in apple trees: Causes, environmental factors, and management - E R, Rashmi; Kishore, Arun; Chandni (Indian Horticulture, 2024)
Burr knots, or burls, are adventitious root formations found on certain apple tree varieties, notably those with specific rootstocks and cultivars like Gala and Empire. While advantageous for propagation due to their rapid root growth, burr knots present challenges in orchard management. This article explores their genetic and environmental triggers, dating back to the 19th century when varieties like Burr knot were favoured for their ability to propagate easily from cuttings. Despite their historical significance, burr knots require careful management to minimize their impact on apple orchard health and productivity. Understanding their causes and implementing proactive management strategies are essential for maintaining healthy apple tree population.